AN ANALYSIS OF ISLAMIC BUSINESS ETHICS AMONG MUSLIM TRADERS WITHIN THE CONTEMPORARY URBAN MUSLIM SOCIETY OF THE CITY OF THOUSAND CHURCHES - Samad, Telsy Fratama Dewi; Adi, Chairul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
Islam recognizes the urge to engage in commercial operations and does not forbid such activities; in fact, business activities can be an element of worship if done according to Islamic code of ethics. This principle becomes particularly relevant in analyzing the business practices of Muslim traders within the contemporary urban Muslim society of the City of Thousand Churches. The purpose of this article is to meticulously map the business practices of urban Muslim traders in the city of a thousand churches, using Rafik Issa Beekun's theory of Islamic business ethics, as well as theory indicators such as unity, equilibrium, freewill, responsibility, and benevolence. This study used a descriptive qualitative method with a phenomenological approach. A total of six informants, consisting of four women and two men who are Muslim traders in urban Manado, were selected to provide in-depth information based on their business experiences within the predominantly non-Muslim society. The data collected from these interviews were analyzed using the framework of Islamic business ethics to explore the ethical practices applied by these traders. The findings of this study demonstrate that practically all informants who operate as traders in the Urban Manado area met the five markers of Islamic business ethics theory. Although two traders' practices do not match the Free Will indicator, this has no substantial impact because they can still be improved through socialization. It may be inferred that, despite the fact that Muslim traders reside in a minority area, trade practices consistent with Islamic business ethics are nonetheless widely practiced by traders in Manado's urban centre, known as the city of a thousand churches.